SISTEM PENDUKUNG KEPUTUSAN DENGAN METODE MOORA UNTUK PEMILIHAN LAHAN PEMBUATAN DRAINASE DI KAWASAN PERTIWI LESTARI INDUSTRIAL ESTATE - Dira Nabila Zahra; Mochzen Gito Resmi; Imam Ma'ruf Nugroho (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
The Pertiwi Lestari Industrial Estate project is a project in 2019, which is located in Trans Heksa Karawang, West Java. The drainage channel is a channel that receives from a local channel or discharge from the factory which will then channel it to a secondary channel, so that water from each factory will not stagnate around the Pertiwi Lestari area and will not cause pollution to the soil and unpleasant odors. Problems that often arise when digging for drainage are the number of slope errors that are miscalculated and do not fit in manual calculations because the priority scale is taken based on the closest location by workers. With the above problems, for the selection of land for drainage, one of which is excavation in the Pertiwi Lestari Industrial Estate area using a decision support system with the Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) method, the method used in this design uses a prototype development model. This system is made using php v 5.6 xampp v3.2.1 codeigniter v 3.1.1.1 with Mysql v 5.1.1 database. For the design of this system is made using the Unified Modeling Language (UML), using the Class Diagram database model. Tests carried out on this system are Black Box Testing. Where for the highest priority for the selection of land for drainage is in block d with a result of 45.1941.